Significant intersections Daugavpils Region Artists Association during from 1998 till 2013 - Folkmane, Mairita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Daugavpils Region Artists Association (DRAA) is a professional creative organization, which now comprises 37 artists from different generations, schools and professional industry: painters, graphic artists, sculptors, textile artists, potters, stage designers, etc. DRAA was founded in 1998. Organization is to promote conditions for creativity, to promote the association's creative work, to defend artists' creative freedom, moral, economic, social rights and professional interests. In its 15 years of existence, Daugavpils Region Artists Association organized exhibitions in Latvia and abroad, promoted the development of visual culture in Latgale and combined local professional artists in their own activities. Besides to those artists actively developed their own individual artistic work through exhibitions, participation in international and Latvian plenaries, residencies and master classes. Significant work has been done documenting the artists' creative work. Artistic activity of the group has seen more active and less saturated periods. At this time DRAA has become significant in the context of Latvian art and has created interest among partners in Lithuania, Belarus, France, etc. Due to the personal initiative DRAA artists exhibited their works in group exhibitions and had solo exhibitions in Lithuania, Belarus, Germany, Estonia, Russia, Austria, Poland, France, Norway, Denmark, Sweden, Spain, Uzbekistan, Finland, Switzerland, Italy. During DRAA existence the artists held around 150 solo exhibitions and participated in over 500 group exhibitions in Latvia and abroad. In period from 1998 to 2013th DRAA implemented various activities related to art, which positively influenced and enriched the cultural life of Daugavpils, contributed to the city and state recognition of cultural space. A leading role in driving of this process belongs to the personalities in the DRAA group – to its leaders Līga Čible and Romualds Gibovskis. Group of artists could achieve its aims only if state and local government will provide a moral and material support in order to develop the area of education, the arts process documentation and work procurement issues. Only cooperation between different institutions can create an attractive and modern cultural facilities on the eastern border. Article aims to collect information on the artists DRAA professional activities from 1998 to 2013th year describe the group of main areas of activity and reflect the most significant achievements.